Efficiency of foreign banks: Evidence from selected (Association of Southeast Asian Nations) ASEAN countries - Chan, Sok-Gee; Abd Karim, Mohd Zaini (Academic Journals, 2011)
This study examined foreign banks efficiency in selected ASEAN countries (Indonesia, Malaysia, the Philippines, and Thailand) for the period of 2001 to 2008 by using the parametric stochastic frontier analysis (SFA) approach.The results indicate that foreign banks originating from developed countries are more cost and profit efficient as compared to foreign banks from developing countries.The results also show that foreign banks in Malaysia are the most cost and profit efficient while foreign banks in Indonesia are the least.The result is consistent with the difference in index of economic freedom over the years between the countries studied.Hence, to attract foreign banks into the ASEAN countries, authorities should liberalize their banking sector.Less restrictive banking sector will allow healthy competition between foreign and local banks in the developing countries resulting in higher overall banking industry efficiency.